An Economic Sociological Look at Economic Anthropology - Aspers, Patrik; Darr, Asaf; Kohl, Sebastian (Journal of Economic Sociology, 2011)
The paper is intended to be a brief introduction into the field of economic anthropology. The authors make an overview of the main issues of the discipline. More specifically, the paper focuses on the foundations of economic anthropology, key debates within the field and the topics the field typically deals with. Some classical works that concern these topics are mentioned. In conclusion, possible fruitful encounters between economic anthropology and economic sociology are described.